Chitosan Oligosaccharides as a Nanomaterial Platform: Biological Properties and Applications in the Biomedical and Pharmaceutical Fields - Razi, Muhamad Alif (UI Scholars Hub, 2022)
Chitosan oligosaccharides (COS) have been introduced as marine-derived biomaterials with potential health benefits and good water solubility properties. This study presents an overview of the promising nanomaterial platform for biomedical and pharmaceutical applications of COS. The health benefits of COS, primarily their antioxidant and protective effects, anti-inflammatory activity, antidiabetic properties, and cholesterol-lowering effects are discussed. Furthermore, the promising recent articles on specific topics such as drug delivery systems and nanobiomaterials, are highlighted